Epigenetic pathways in PTSD: How traumatic experiences leave their signature on the genome - Tania L. Roth (Frontiers Research Topics, 2015)
This research topic focuses on epigenetic components of PTSD. Epigenetic mechanisms are a class of molecular mechanisms by which environmental influences, including stress, can interact with the genome to have long-term consequences for brain plasticity and behavior. Articles herein include empirical reports and reviews that link stress and trauma with epigenetic alterations in humans and animal models of early- or later-life stress. Themes present throughout the collection include: DNA methylation is a useful biomarker of stress and treatment outcome in humans; epigenetic programming of stress-sensitive physiological systems early in development confers an enhanced risk on disease development upon re-exposure to trauma or stress; and, long-lived fear memories are associated with epigenetic alterations in fear memory and extinction brain circuitry.